2008
DOI: 10.1007/s11434-008-0412-4
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and mechanism of the adsorption/desorption of tectonically deformed coals

Abstract: The physical and chemical texture of tectonically deformed coals produced by various formational mechanisms are different from those of primary coals, thus resulting in major differences among the physical properties of the reservoirs of these coals. We have studied the adsorption/desorption behavior of tectonically deformed coals by the use of isothermal adsorption/desorption experiments under equilibrium moisture condition. Experiments of isothermal adsorption/desorption of methane or multi-component gases h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 18 publications
0
45
0
1
Order By: Relevance
“…After doing mercury intrusion experiments on 12 coal samples, Zhou and Wu (2012) discovered the "U"-shaped change of porosity and pore volume with the degree of metamorphism, with R O,ran = 2.0 % as the dividing point. Tectonic deformation can cause significant changes in the physical and chemical structures of coal Ju et al 2009;Li et al 2012;Hou et al 2012), resulting in subsequent changes in pore characteristics and even nanoscale pore structures (Ju et al 2005). Through mercury intrusion experiments on Pingdingshan tectonically deformed coal in China, Ogawa 2001, 2003) noted that the porosity in the tectonically deformed coal was 3-8 times higher than the normal structure coal in the same location and the specific surface area of pore is 2-10 times higher.…”
Section: Introductionmentioning
confidence: 99%
“…After doing mercury intrusion experiments on 12 coal samples, Zhou and Wu (2012) discovered the "U"-shaped change of porosity and pore volume with the degree of metamorphism, with R O,ran = 2.0 % as the dividing point. Tectonic deformation can cause significant changes in the physical and chemical structures of coal Ju et al 2009;Li et al 2012;Hou et al 2012), resulting in subsequent changes in pore characteristics and even nanoscale pore structures (Ju et al 2005). Through mercury intrusion experiments on Pingdingshan tectonically deformed coal in China, Ogawa 2001, 2003) noted that the porosity in the tectonically deformed coal was 3-8 times higher than the normal structure coal in the same location and the specific surface area of pore is 2-10 times higher.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that the gas adsorption and desorption properties of coal-like materials were consistent with those of the natural coal and could meet the test requirements [6]. Coal has a strong gas adsorption capacity mainly because of its good porosity and relatively large specific surface area [36,37]. Therefore, under the same molding pressure conditions, the coal mass ratio had the most impact on these characteristics.…”
Section: Adsorption and Desorption Parametersmentioning
confidence: 54%
“…This is mainly because TDC is formed under mono-or multi-phase strong tectonic movements. Its original structure has been deformed or damaged, resulting in larger adsorption surface area and higher gas content than the primary coal [37]. In this paper, the natural coal samples were selected from a typical tectonically deformed coal seam from No.…”
Section: Preparation and Testing Of Natural Coal Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…St. George and Barakat [26] studied the coal deformation during sorption and desorption of different gases under uniaxial pressure. Ju et al [27] found through experiments that the desorption curve conforms to the Langmuir equation when the degree of coal deformation is low, but not when the degree of coal deformation is high. Liu et al [28,29] experimentally studied the swelling deformation of coal induced by gas sorption using a self-developed testing apparatus based on coal solid-gas coupled mesomechanics and discussed the dynamic process of expansion deformation due to sorption of gas under different pressures, the anisotropy of sorption deformation, and the relationship between sorption deformation value and gas sorption amount.…”
Section: Introductionmentioning
confidence: 99%